2022
DOI: 10.1016/j.biopsych.2021.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Prenatal Anxiety and the Fetal Origins of Epigenetic Aging

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 43 publications
2
27
2
Order By: Relevance
“…Here, we adopted indirect markers of prenatal glucocorticoid and inflammation exposure, obtained by DNAm levels in sensitive CpGs sites. Previously, using two different cohorts, prenatal anxiety was not associated with the epigenetic proxy of glucocorticoid exposure [ 6 ]. In our findings, maternal feeling related to pregnancy was not a GAA predictor in the model considering the GES, being significant only in the i-ePGS model, even though the presence of maternal history of mental disorder contributed to both models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, we adopted indirect markers of prenatal glucocorticoid and inflammation exposure, obtained by DNAm levels in sensitive CpGs sites. Previously, using two different cohorts, prenatal anxiety was not associated with the epigenetic proxy of glucocorticoid exposure [ 6 ]. In our findings, maternal feeling related to pregnancy was not a GAA predictor in the model considering the GES, being significant only in the i-ePGS model, even though the presence of maternal history of mental disorder contributed to both models.…”
Section: Discussionmentioning
confidence: 99%
“…To detect overexposure to inflammation or glucocorticoids during gestation requires complex study designs and it is challenging matter. As DNAm presents marks of environmental experiences, some studies have proposed epigenetic scores that can reflect these exposures [ 6 , 7 ]. DNAm in specific CpGs can also be used to build epigenetic clocks capable of predicting the chronological age of a sample with relative accuracy [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous animal studies have shown that long-lasting epigenetic changes caused by prenatal stress involve gene encoding BNDF, the corticotropin-releasing factor (Crf), and the glucocorticoid receptor (Nr3c1), which is associated with the HPA axis (Mueller and Bale, 2008 ; Dong et al, 2015 ). Recent clinical studies have found that prenatal maternal anxiety predicts accelerated epigenetic age in children in the experimental cohort and reveals increased sensitivity in men rather than woman in regared to the fetal origins of epigenetic age acceleration (Mcgill et al, 2022 ).…”
Section: The Effects Of Ee On Neurodevelopment In Brainmentioning
confidence: 99%